PERSEPSI MASYARAKAT TERHADAP PELAYANAN E-KTP DI BREBES - Ardiansyah , Aqib; Anis, Aswhar (AMERTA Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2022)
This study aims to describe the public perception of E-KTP servants in Brebes city. The indicators in this study are the simplicity of service procedures, clarity of services (from requirements, work units and service fees), the timeliness of completion of services, product and process safety, facilities and services, as well as access to places and locations of services. The research method uses qualitative descriptive. The source of primary data is obtained by using purposive sampling technique, to determine some people who are consifered to really master the problem related to this research. The study illustrate that public perceptions of E-KTP servants in Brebes city from the simplicity of procedures are not easily understood by the community. Clear service clarity of clear requirements, responsive work units, and free service fees. in accordance with the determined schedule. Product and process safety. Insufficient infrastructure facilities. As well as the place and location of services that are easily accessible in the E-KTP service in the Brebes city. Keywoards: community perception, E-KTP service, Brebes City